2010
DOI: 10.3109/0142159x.2010.528809
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the systems-based practice requirement with health policy content and educational technology

Abstract: Duke University Hospital Office of Graduate Medical Education and Duke University's Fuqua School of Business collaborated to offer a Health Policy lecture series to residents and fellows across the institution, addressing the ''Systems-based Practice'' competency.During the first year, content was offered in two formats: live lecture and web/podcast. Participants could elect the modality which was most convenient for them. In Year Two, the format was changed so that all content was web/podcast and a quarterly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…• Projects are being shared and published in peer-reviewed venues and academic journals, [9][10][11][12][13][14][15][16][17][18][19][20] and several others are in preparation for submission or awaiting journal decisions. A few institutions have responded by providing seed money to allow teaching faculty time for educational innovation.…”
Section: Impactsmentioning
confidence: 99%
“…• Projects are being shared and published in peer-reviewed venues and academic journals, [9][10][11][12][13][14][15][16][17][18][19][20] and several others are in preparation for submission or awaiting journal decisions. A few institutions have responded by providing seed money to allow teaching faculty time for educational innovation.…”
Section: Impactsmentioning
confidence: 99%
“…Few publications describe existing health policy curricula at the undergraduate medical education or GME level (Bischof, et al, 1996;Short & Hodgetts, 1997;Furin, et al, 2006;Foster, et al, 2008;Strelnick, et al, 2008;Nagler, et al, 2010;Chick, et al, 2014). Despite calls for more emphasis on the "social, economic, and political aspects of health care delivery" from medical educators (Cooke, et al, 2006) and recent interest in learning health policy, leadership, and medical economics by students, perceived education in health policy remains unacceptably low (Patel, et al, 2014).…”
Section: Lack Of Medical Education In Health Policymentioning
confidence: 99%
“…However, Hadley et al, Nagler et al, and Vogt et al, reported no significant differences in exam scores between students receiving in-person and online content delivery. (Hadley et al, 2010;Nagler, Andolsek, Dossary, Schlueter, & Schulman, 2010;Vogt et al, 2010) While the student viewpoint and opinions of these technologies have been frequently studied, to date there has been little reported on how faculty perceive these technologies. One faculty concern is decreased student attendance in class.…”
Section: Literature Reviewmentioning
confidence: 99%